Music as a methodological teaching tool (Research, Society and Development, 2023)
Music has been an essential part of the transmission of knowledge since time immemorial, being part of the construction of knowledge and a way of transmitting it and of history itself. However, as education has gone through institutionalization processes, it has lost this important transcendental tool and is no longer used as a teaching tool. Thus, this paper presents an investigation into the use of music as a teaching-learning method. The justification for this work is the very cultural formation of the human being, always based, since the beginning, on music, dance, and conversations, which was the teaching method when knowledge was passed from generation to generation. The use of music has been presented since the Greeks as a discipline necessary for the formation of the individual, losing its important space only after the advent of public schooling and the need for practical training. The disciplines with the intention of human formation have increasingly lost their space. It is necessary to revive the importance of the use of music as an essential tool for teaching. The general objective of this work was to understand how music can be used as a teaching-learning tool in elementary school, considering the classes of natural sciences in the public school system. The methodology used was bibliographic research as a basic theoretical basis and qualitative field. The final results of this work were that the authors agree on the importance of music for the development of knowledge and especially in innovation in the transmission of knowledge, even though the biological sciences are a more precise area of knowledge, it can still have more sensitive tools for its transmission, and music is an important tool. The focus of this work was to better understand music and its use in the teaching learning process and the possibilities present today. Music is closely linked to the individual being and his formation as a subject.